Effects of situated learning and clarification of misconceptions on contextual reasoning about natural selection - Helena Aptyka; Daniela Fiedler; Jörg Großschedl (Evolution: Education and Outreach, 2022)
Abstract Background Natural selection is a core principle of evolution. Understanding natural selection enables students to think about the evolution and the variability of life. Despite its great importance, understanding natural selection is challenging for students. This is evident in the phenomenon of contextual reasoning, showing that students can often explain natural selection in one context (e.g., trait gain) but not in another (e.g., trait loss). The study pursues the following aims: First, to examine the link between contextual reasoning and situated learning. Second, to explore whether different instructional strategies differ in their associated cognitive load. Third, to investigate whether clarifying common misconceptions about natural selection (no vs. yes) is an effective strategy to regular instructions when aiming to increase key concepts and reduce misconceptions. Fourth, to exploratively examine the effectiveness of different instructional strategies. Method In a 2 × 2 factorial intervention study with a total of N = 373 secondary school students, we varied the instructional material of a 90-min intervention in terms of the evolutionary context (trait gain vs. trait loss) and the availability of additional support in the form of a clarification of misconceptions (no vs. yes). We measured students’ cognitive load immediately after instruction and assessed their ability to reason about natural selection (i.e., use of key concepts and misconceptions) later. Results We documented low knowledge about evolution in the pre-test and persisting misconceptions in the post-test. The results showed that the intervention context of trait loss elicited a higher intrinsic and extraneous cognitive load than trait gain. Moreover, when the clarification of misconceptions is analyzed in connection to the intervention context, it reveals a potential for reducing misconceptions in some contexts. Students who have learned in trait gain contexts with a clarification used significantly fewer misconceptions in later reasoning than students who learned in trait gain contexts without a clarification of misconceptions. Conclusion Our study creates new insights into learning about natural selection by outlining the complex interplay between situated learning, cognitive load, clarification of misconceptions, and contextual reasoning. Additionally, it advises researchers and educators on potential instructional strategies.